ENERGIYA SIYOSATI VA "YASHIL" IQTISODIYOTGA O'TISH - Xolyigitov Sherzod Faxriddin o’g’li, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abctract: This article is devoted to the development of the green economy in the Republic of Uzbekistan and analyzes new directions in ensuring sustainable economic growth and environmental safety in the country. The basic principles of the green economy, their application in Uzbekistan, and the role of green energy in this process are discussed. The article highlights the current state of the green energy system in Uzbekistan, ongoing innovative projects to improve energy efficiency and use renewable energy sources. He also examines the economic and social significance of the transition to a green economy, the importance of maintaining environmental sustainability and taking action against global climate change. The article is aimed at defining the strategic goals of Uzbekistan in the field of green energy and practical steps that need to be taken towards sustainable development through them.